1999
DOI: 10.1161/01.res.85.10.906
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Matrix Metalloproteinase-2 Cleaves Big Endothelin-1 Yielding a Novel Vasoconstrictor

Abstract: Abstract-Matrix metalloproteinase-2 (MMP-2, gelatinase A) and its tissue inhibitor (TIMP-2) are mainly known for their roles in the (patho)physiological remodeling of the vasculature, angiogenesis, tissue repair, tumor invasion, inflammation, and atherosclerotic plaque rupture. A mechanism of action of MMP-2 is the proteolytic breakdown of specific extracellular matrix proteins. The amino acid sequences in interstitial collagen (Gly-Leu/Ile) and laminin-5 (Ala-Leu) that are cleaved by MMP-2 are homologous to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
231
3
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(252 citation statements)
references
References 28 publications
10
231
3
8
Order By: Relevance
“…19,20,58 Our data demonstrate that active MMP-1 is also a regulator of vascular reactivity. Therefore, increasing levels of MMP-1 in preeclampsia seem to be central to the hypertensive disorder observed in these women.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…19,20,58 Our data demonstrate that active MMP-1 is also a regulator of vascular reactivity. Therefore, increasing levels of MMP-1 in preeclampsia seem to be central to the hypertensive disorder observed in these women.…”
Section: Discussionmentioning
confidence: 53%
“…19,20,36 To ascertain whether MMP-1 has a role in the regulation of vascular reactivity, active enzyme was perfused into the lumen of intact omental arteries at varying concentrations and tested for vasoconstriction using a myograph system. We found that activated MMP-1 directly caused vessel contraction at 0.25 ng/ml (P Ͻ 0.05), 2.5 ng/ml (P Ͻ 0.001), and 25 ng/ml (P Ͻ 0.001) ( Figure 5).…”
Section: Mmp-1 Induces Vasoconstriction Via Par-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Both are further processed into ET-1 by neutral endopeptidase (NEP). [17][18][19] Thus, a dual NEP/ECE inhibitor, for example the novel compound SOL1, reduces ET-1 production by inhibiting all three pathways. 20 Recently, Kalk et al 21 reported that the dual NEP/ECE inhibitor daglutril (SLV338, an analog of SOL1) reduced cardiomyocyte hypertrophy, interstitial fibrosis and perivascular fibrosis in the 2-kidney 1-clip model of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…transforming growth factor-β (TGF-β)), cell surface receptors (e.g. β2-adrenergic receptor, vascular endothelial growth factor receptor-2 (VEGFR-2), insulin receptor) and extracellular matrix components [2][3][4][5][6][7][8][9][10]. We review here emerging evidence that MMPs and ADAMs are key mediators that might regulate one another (e.g.…”
Section: Introductionmentioning
confidence: 99%